Antibacterial Activity and Mechanism of Litsea cubeba Essential Oil Against Salmonella typhimurium - Cuncai Wang; Xiying Chen; Mingjie Liu; Xiaoquan Tang; Youzhi Li; Yuming Zhan; Zhihui Hao (Plants)
Litsea cubeba essential oil (LCEO) has been reported as an antibacterial agent, but its effects against Salmonella typhimurium (S.Tm) and the underlying mechanisms remain unclear. The antibacterial efficacy of LCEO was assessed utilizing both microdilution and growth curve methodologies, and its chemical composition was thoroughly analyzed. Morphological alterations in the cells were observed through scanning electron microscopy (SEM), while cellular permeability was gauged based on the variations in nucleic acid and protein contents. The impact of LCEO on ATPase activity and its anti-biofilm formation activity was assessed using colorimetric methods. The results indicated that the MIC and MBC of LCEO against S.Tm were 0.4 mg/mL and 0.8 mg/mL, respectively. SEM and PI staining revealed disrupted bacterial cell integrity. Compared to those in the control group, treatment with LCEO significantly elevated the levels of extracellular nucleic acids and proteins (p < 0.05). Furthermore, at the MIC, LCEO led to a 77.9% reduction in AKP content, and decreased intracellular Na+K+-ATPase and Ca2+Mg2+-ATPase activities by 79.9% and 54.6%, respectively. Additionally, LCEO markedly inhibited biofilm formation, enhanced surface hydrophobicity, and diminished the swimming motility of S.Tm. Overall, LCEO exhibited promising antibacterial properties, indicating its potential as an effective inhibitor against S.Tm.